Nontraumatic Emergency of the Spine - LLopis, Eva; Belloch, Elena; Gallegos, Paulina; Higueras, Victoria; Taberner, Esther (Seminars in Musculoskeletal Radiology, 2017)
Nontraumatic spinal emergencies can have many different causes. Clinical symptoms may be nonspecific, and therefore radiology plays a key role in diagnosing and managing these patients. There is considerable time pressure in these situations because the development of irreversible myelopathy depends not only on the cause but also on the time elapsed between the start of compression and the decompression. To avoid structural cord damage, decompression should be done within 6 to 8 hours after the start of the compression. If patients still walk when the lesion is detected, they have a 90 to 100% chance of walking when the lesion is treated immediately.Magnetic resonance imaging is the primary method for the evaluation of spinal emergencies. An appropriate fast protocol should be used, adding some special sequences depending on the clinical scenario.In this review we use a simple anatomical approach that can be applied in an acute practical clinical setting, allowing an accurate differential diagnosis that will guide subsequent therapeutic actions. We highlight key radiologic features that will help nonspecialized radiologists make a precise diagnosis.
Keywords: spinal cord; intramedullary lesions; extramedullary lesions; intradural-extramedullary lesions; extradural-extramedullary lesions; spinal cord emergencies